Appropriate sawing techniques for improving teak log (Tectona grandis) from plantation in Lao PDR - Bouaphavong, Douangta; Jarusombuti, Songklod; Veenin, Teera; Phonetip, Khamtan (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
The aim of this research is to evaluate log recovery in teak (Tectona grandis) lumber production by three sawing machines (circular saw, vertical band saw, and horizontal band saw) and three sawing patterns (lumber sawn from squared lumber sawing, plain sawing, and quarter sawing). Total 90 teak logs harvested from plantation in Laos were used for the experiment. In plain sawing pattern, vertical band saw was 68.21%, 68.20% in horizontal band saw and 65.48% in circular saw. The second level of log recovery was lumber sawn from squared lumber: 56.29% in horizontal band saw, 55.56% in circular saw, and 40.07% in vertical band saw. There was significant difference (p < 0.05) among three sawing patterns. Statistical comparison between three techniques sawing was high significant differences which plain saw was maximum volume of lumber. Three wood machineries comparison only time significantly the circular saw was spend time less than both band saw. It is suggested that flat sawing patterns with horizontal band saw or circular saw was very useful in regard as log recovery for teak lumber production.